Analisa Respon Masyarakat Muslim Kota Medan Terhadap Asuransi Syariah - Yudi Setiawan (AT-TAWASSUTH: Jurnal Ekonomi Islam, 2018)
The purpose of this study was to see the general public's response to insurance in Medan. The variables used in this study are service variables, income and the response of the people of Medan City. The data used in this study are primary data through direct interviews and questionnaires with a sample of 100 respondents spread across 4 sub-districts of Medan City, namely Medan Kota sub-district, Medan Petisah sub-district, Medan Tembung sub-district and Medan Denai sub-district. While the data analysis techniques of this study are multiple regression with the Ordinary Least Square method. The results show that the service and income variables significantly influence both simultaneously and partially on the response of the Medan City Muslim community in Islamic insurance. The results also show that service and income variables can explain the response of the Medan City Muslim community as much as 65.6% while the remaining 34.4% is explained by other factors. The need for education and socialization of sharia insurance and also the increasing professionalism of sharia insurance agents is the solution so that the response of Muslim communities increases especially in the city of Medan.